Table of Content and Foreword of the MIMBAR PENDIDIKAN Journal, issue of March 2016 - Mimbar Pendidikan, Editor Journal (MIMBAR PENDIDIKAN, 2016)
This journal was firstly published on March 11, 2016 by UPI (Indonesia University of Education) Press in Bandung. The MIMBAR PENDIDIKAN  is a new version journal from the old journal with the similar name that was published since 1995 to 2005. This journal is dedicated not only for Indonesian scholars who concern about educational studies, but also welcome to the scholars of Southeast Asian countries and around the world who care and share related to the educational studies in general. The MIMBAR PENDIDIKAN journal is published twice a year i.e. every March and September. Bandung, Indonesia: March 11, 2016. Prof. H. Furqon, M.A., Ph.D.Honorable Patron of the MIMBAR PENDIDIKAN Journal; and Rector of UPI (Indonesia University of Education) in Bandung.